Productivity Shocks and Repayment Behavior in Rural Credit Markets : A Framed Field Experiment - Adjognon, Guigonan Serge (World Bank, Washington, DC, 2018)
Improving rural credit markets requires a good understanding of the root causes of market failures and taking necessary steps to address them. This paper investigates the role of productivity shocks in borrowers' repayment choices. Using a framed field experiment that simulated a repeated interaction in an input credit market, the analysis finds strong evidence that negative productivity shocks lead to higher default, even when they do not induce negative returns. This relationship is robust to the presence of an information exchange system enforcing dynamic incentives. The findings suggest that recurrent agricultural production shocks resulting from the negative effects of climate change could exacerbate failures in rural credit markets, undermining hard-won progress toward rural financial inclusion.